Analyst Reaction to War-Related Language: Source Domains and the Role of Market Structure and Market Share - Cotter Salvado, João; Crilly, Donal (Organization Science, 2025)
Corporate executives often use metaphors, particularly those derived from war imagery, when communicating their strategic intentions. This study examines the influence of metaphorical framing in corporate communication, particularly its effect on analyst reactions to firms’ acquisition announcements. We theorize and analyze the impact of metaphor families that either emphasize or downplay competition while considering the diverse source domains from which these metaphors originate. We propose a theoretical framework that integrates conceptual metaphor theory with the risk-as-feelings perspective, suggesting that certain metaphors can evoke visceral perceptions of danger. Our findings reveal that using metaphors in acquisition announcements generally elicits negative reactions. Notably, metaphors from the competition family, especially war-related ones signifying competitive aggression, evoke stronger adverse reactions. The detrimental impact of war language substantially diminishes in contexts where aggressive competition is expected. We contribute to strategic communication research by highlighting the contingent influence of metaphorical framing on audience reactions, emphasizing the importance of metaphor families, source domains, and contextual factors. Funding: J. C. Salvado acknowledges funding through the FCT – Foundation for Science and Technology, I.P., within the scope of the grant “UID/GES/00407/2020”. D. Crilly was supported by the H2020 European Research Council [Grant 820075].